2004
DOI: 10.1108/00214660480001161
|View full text |Cite
|
Sign up to set email alerts
|

Competition in farm credit markets: identifying market segments served by the farm credit system and commercial banks

Abstract: Agricultural credit markets are dominated by two institutional retail lender groups, the cooperative Farm Credit System (FCS) and commercial banks. Analysis of farm loans made over the 1991S1993 and 2001S2002 periods indicates that FCS lenders were more likely to serve full‐time commercial farmers and farmers located in regions with less competitive credit markets. In contrast, commercial banks were more likely to serve small, part‐time, and hobby farmers. This segmentation of farm credit markets is consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
1
10
0
1
Order By: Relevance
“…The results regarding the impact of other lenders and type of loans – real estate backed (lagged values) and non-real estate loans – are compatible with previous findings by Dodson and Koenig (2004) and support the market segmentation hypothesis that the FCS institutions lend to larger full-time farmers while financing from alternative sources may be used for activities other than farming or for part-time farming and thus its impact is not captured by these dependent variables[5].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results regarding the impact of other lenders and type of loans – real estate backed (lagged values) and non-real estate loans – are compatible with previous findings by Dodson and Koenig (2004) and support the market segmentation hypothesis that the FCS institutions lend to larger full-time farmers while financing from alternative sources may be used for activities other than farming or for part-time farming and thus its impact is not captured by these dependent variables[5].…”
Section: Resultssupporting
confidence: 83%
“…These studies suggest that the credit needs of part-time farmers are different from those of full-time commercial farmers necessitating the existence of the FCS. Dodson and Koenig (2004) found that indeed FCS institutions are more likely to serve full-time commercial farmers and farmers located in regions with less competitive credit markets, while commercial banks were more likely to serve small, part-time, and hobby farmers. The authors conclude that this market segmentation of farm credit markets is consistent with expectations because federal regulations require FCS to provide credit to the “bona fide” farmers.…”
Section: Previous Literaturementioning
confidence: 99%
“…Also, overall model significance would imply that FSA guarantees do not completely mitigate the relative comparative advantages in lending technologies of large and small banks. The framework used for this analysis was similar to approaches used in previous studies (Berger and Black, 2011;Dodson and Koenig, 2004;Wedel and Kamakura (2000); Black and Schweitzer, 1981). Berger and Black, in particular, utilized a similar empirical framework to analyze the probability that a small business loan was made by a small or large bank.…”
Section: Commercial Banks and Fsa-guaranteed Loan Programsmentioning
confidence: 98%
“…Finansowanie podmiotów sektora rolnego jest praktycznie na całym świecie relatywnie trudnym wyzwaniem dla kredytodawców, co wynika ze znacznego poziomu ryzyka związanego z produkcją rolniczą (Dodson, Koenig 2004;Turvey 2013;Dodson 2014;Hartarska Nadolnyak, Shen 2015). Wymaga to też nader subtelnego zaangażowania ze strony państwa (Turvey 2013).…”
Section: Wprowadzenieunclassified